Gender relations in the workplace: The experience of female managers in African harbours - (:unkn) unknown (My University, 2019)
Scholarship on women in management has been dominated by White Western women, rendering African women management research largely invisible. Consequently, we know very little about female managers in African contexts. This study advances knowledge of the career obstacles, work–life balance issues and leadership styles of African women leaders, by presenting testimonies based on exploratory qualitative interviews with 26 female port managers from two North African countries and eight sub-Saharan countries. The findings show that the interviewees in this sample are not subjugated women on the periphery of their societies. Rather, they are active agents who are capable of producing effective professional identities and mostly represent middle- or upper-class women in their societies. Although they face similar issues as those identified in previous women in management literature, including subtle or overt discrimination, work–life balance difficulties and a lack of recognition from male counterparts, their situation differs slightly from those in the West owing to their cultural, historical and religious context.
Keywords: African Research